Binary acoustic trapping in a glass capillary. (21st June 2021) - Fornell, Anna; Baasch, Thierry; Johannesson, Carl; Nilsson, Johan; Tenje, Maria
Abstract: Acoustic trapping is a useful method for handling biological samples in microfluidic systems. The aim of this work is twofold: first to investigate the physics behind acoustic trapping in a glass capillary and secondly to perform binary acoustic trapping. The latter is achieved by increasing the density of the fluid in the trapping channel. The trapping device consisted of a glass capillary with a rectangular inner cross-section (height 200 µ m × width 2000 µ m) equipped with a small piezoelectric transducer. The piezoelectric transducer was actuated at 4 MHz to generate a localised half-wavelength acoustic standing-wave-field in the capillary, comprising of a pressure field and a velocity field. Under acoustic actuation, only particles with higher density than the fluid, i.e. having a positive dipole scattering coefficient, were trapped in the flow direction. The numerical and analytical modelling of the system show that the trapping force which retains the particles against the flow depends only on the dipole scattering coefficient in the pressure nodal plane of the acoustic field. The analytical model also reveals that the retention force is proportional to the dipole scattering coefficient, which agrees with our experimental findings. Next, we showed that in a mixture of melamine particles and polystyrene particles in a high-density fluid it is possible to selectively trap melamine particles, since melamine particles have higher density than polystyrene particles.